A Characterization Study of a Nanowire-Network Transistor with Various Channel Layers - Jang, J; Cha, S; Butler, T; Sohn, J; Kim, J; Jin, Y; Amaratunga, G; Jung, J; Kim, J (2009)
The performance of a ZnO network transistor is studied by means of the change in threshold slope with varying number of nanowire channel layers. The threshold slope broadens as the number of layers in the channel increases and, in the case of a two-layer channel, a double turn-on effect can be observed. The gatefield simulation shows gate-field distortion by the surface of the nanowire. © 2009 WILEY-VCH Verlag GmbH and Co. KGaA.